Streamlining India's democratic landscape: An empirical study into ' One Nation One Election(ONOE) policy - Kumar, Suresh & Bansal, Meenakshi (Indian Journal of Political Science)
The concept of 'One Nation One Election' originated from the desire to have improved governance by aligning the state and the central electoral calendars. This empirical study aims to explore the many facets of the 'One Nation One Election' policy in an effort to gain a comprehensive understanding of its possible effects on Voter in India democracy. The study uses a data-driven methodology to examine the implications of this policy. A mixed method technique is adopted in this research paper where firstly Google from was send to 83respondents of various demographic segments in order to get quantitative data on opinions on 'One Nation One Election' policy in India. Important issues including how synchronized elections would impact voter turnout, whether election-related spending may be cut and other related dimensions are covered in this research paper. There are various possible challenges related to 'One Nation One Election' policy in India such as management of midterm election in government collapse, coordinating so many at once might be challenging, Central issue can overshadow the state issue and many others. To resolve these, there would be a urgent need to spread awareness about the benefits of it to the public, government should not be in hasted to implement this policy as it may lead to power concentration and all other possible alternative available according to the time. The present research was motivated to give empirical data based insights into the impacts of voter on ONOE policy in India as there is a noticeable gap in this regard. This through investigation seeks to contribute to the current discussion about the electoral changes in India.
Keywords: One Nation One Election, ONOE, Democracy, Election, India, Nation, One, Voter